Safe Movement, Comfortable Living: Optimizing Health and Productivity among Older Adults at RPTRA Masudela, Sawah Besar District - Ratu Chairunisa; Elyn A. K. Lumban Gaol; Astrid Komala Dewi; Afifah Nur Azizah; Kayla Salina (AMK : Abdi Masyarakat UIKA, 2026)
Falls remain one of the most frequent health concerns among older adults, often affecting mobility, independence, and overall well-being. Limited understanding of fall risk factors may increase the likelihood of accidents and reduce participation in daily activities. This community service activity was conducted to improve older adults’ knowledge of fall prevention, safe movement, mobility maintenance, and productive aging. The program took place on June 2, 2026, at RPTRA Masudela, Sawah Besar District, Central Jakarta, and involved 30 female participants aged 60–68 years. The activity consisted of health education sessions, interactive discussions, balance and mobility exercise demonstrations, and knowledge assessments using pre-test and post-test questionnaires. Participants received information on common causes of falls, preventive strategies in everyday life, and the importance of maintaining physical activity in later years. Following the intervention, participants showed a noticeable improvement in their understanding of the topics presented. The average knowledge score increased from 62 before the activity to 88 after the intervention. In addition, more participants achieved good and very good knowledge categories in the post-test assessment. These results suggest that combining health education with practical exercise demonstrations can be an effective approach to increasing awareness of fall prevention and encouraging active aging among older adults.